Improving community support for older people's needs through commissioning third sector services: a qualitative study. Issue 2 (April 2019) - Chadborn, Neil; Craig, Chris; Sands, Gina; Schneider, Justine; Gladman, John
Aim: This exploratory study of commissioning third sector services for older people aimed to explore whether service data was fed back to commissioners and whether this could improve intelligence about the population and hence inform future commissioning decisions. Background: Third sector services are provided through charities and non-profit community organizations, and over recent years services have developed that assess and advise people for self-management or provide wellbeing support in the community. Third sector services have an opportunity to reach vulnerable populations and to provide intelligence about them. Some third sector services are state funded (commissioned) in the United Kingdom. While evidence is available about the commissioning of statutory health and social care, as well as private providers, there is limited evidence about how third sector health services are funded. Methods: Participants were recruited from commissioner organizations and third sector organizations, both with an interest in supporting the independence, self-management and wellbeing of older people. Organizations were recruited from five purposively selected sites within one region of England (East Midlands). Semi-structured interviews explored the relationships between commissioners and providers and the nature of funding arrangements, including co-production. Interviews also explored collection of data within the service and how data were fed back to commissioners. Focus groups were held with older people with the potential to benefit from wellbeing services. Results: Commissioning arrangements were varied, sometimes complex, and often involved co-production with the third sector. Commissioners valued third sector organizations for their engagement with the local community, value for money, outreach services and ability to provide information about the community. Assessing the needs and outcomes of individuals was integral to delivery of support and advice to older people. Diverse approaches were used to assess an individual's needs and outcomes, although there were concerns that some assessment questionnaires may be too complex for this vulnerable group. Assessment and outcomes data were also used to monitor the service contract and there was potential for the data to be summarized to inform commissioning strategies, but commissioners did not report using assessment data in this way, in practice. While the policy context encouraged partnerships with third sector organizations and their involvement in decision making, the relationship with third sector organizations was not valued within contract arrangements, and may have been made more difficult by the tendering process and the lack of analysis of service data. Conclusion: This exploratory study has demonstrated a diversity of commissioning arrangements for third sector services across one region of England. Most commissioners invited co-production; that is, the commissioners sought input from the third sector while specifying details of the service. Service data, including assessments of needs and outcomes, were reported to commissioners, however commissioners did not appear to use this to full advantage to inform future commissioning decisions. This may indicate a need to improve measurement of needs and outcomes in order to improve the credibility of the commissioning process.